ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PERBANKAN DI INDONESIA - Ika Listyawati; Ida Kristiana (Universitas Muhammadiyah Semarang, 2018)
Corporate governance is still a major problem during financial periods such as Indonesia. Especially, financial institutions have carried out reforms to improve goals and stakeholders. The purposeof this study is to measure corporate governance and in a banking environment that is specific to corporategovernance.The independent variables used in this study are ownership structures consisting of controllingshareholder ownership, foreign ownership, government ownership; the size of the board of directors; the sizeof the board of commissioners; independent commissioner; CAR. The sample of this study is a general bankingcompany located in Indonesia which is listed on the Indonesia Stock Exchange (BEI) for the period 2010-2014.This research data is derived from the annual report of the bank (annual report) for the period 20102014 whichis obtained fromthewebsiteof eachof the banks, theIndonesianBankingDirectory,Indonesian Capital Market Directory(ICMD).Theanalyticalmethodusedismultiple linear regression in accordance with the research objectives that analyzethe effect of independent variables on the dependentvariable. Thepurposivesamplingmethodisusedtodeterminethesampleofchoice.Fro this method,get26 samples of commercial banks.The results of the analysis found that Controlling Shareholder Ownership (OWN) andGovernment Ownership (GOV) showed a negative relationship not significant to banking performance.However, for Foreign Ownership (FOR), Board of Directors Size (BOD), Board of Commissioners Size(BOC), Proportion of Independent Commissioners (INDEP) shows a positive and significant relationship.Then for the variable Capital Adequacy Ratio (CAR) there is a significant negative relationship.